Analysis of Declining Birth Rates in South Korea - Defandri, Wendi; Murialti, Neng; Hidayat, Muhammad (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2024)
The decline in the total fertility rate in South Korea has reached the lowest position worldwide, in 2022 the total fertility rate is 0.78 children per woman. This study aims to see the effect of the number of marriages, the number of elderly population, divorce rates, and house prices on the total fertility rate in South Korea. By taking several samples of areas namely the metropolitan cities (???) of Kwangju, Deajon, and Ulsan. Special self-governing city (?????) of Sejong, Gangwon Province (???), North Jeolla Province (????), and Special Self-Government Province (?????) of Jeju. This study used Korean Statistics data (KOSIS ??????) with a panel data test tool (Data pool). The results of this study show that the factors of the decline in the total fertility rate in South Korea are reduced marriage rates and soaring elderly population.